Total virtual workflow in CAD-CAM bony reconstruction with a single step free fibular graft and immediate dental implants. Issue 9 (November 2018) - Zweifel, D.; Bredell, M.G.; Essig, H.; Gander, T.; Lanzer, M.; Rostetter, C.; Rücker, M.; Studer, S.
Abstract: The Surgical reconstruction of defects of the face is challenging. Local and regional flaps have an important part to play, but large defects of bone and soft tissue are a greater problem. Microvascular tissue transfer has become the standard for such patients, and preoperative planning of bony reconstructions is now common. To use these preplanning tools best the implants should be placed in the prosthetically ideal place, and the bone positioned to surround the implants – that is, truly backward planning of the position of the bone. The buccolingual angulation and the actual position of the implants during operation can be difficult to verify. Using commonly available software and 3-dimensional printing solutions, therefore, we have constructed an algorithm to optimise the position of these implants during the operation, and to get their position as close to the planned outcome as possible. This algorithm is adaptable to any implant system and is potentially possible in any implant or preplanning software unit.